2018
DOI: 10.5604/01.3001.0012.6667
|View full text |Cite
|
Sign up to set email alerts
|

Tribological study of low friction DLC:Ti and MoS2 thin films

Abstract: Purpose: The purpose of this article is to characterize and compare the microstructure and tribological properties of low friction DLC:Ti and MoS2 thin films deposited on the austenitic steel X6CrNiMoTi17-12-2 substrate. Design/methodology/approach: In the research, the samples of the DLC:Ti and MoS2 thin films deposited by PACVD technology and magnetron sputtering method respectively were used. Observations of topography were made using atomic force microscope (AFM). Adhesion of the coating to the substrate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…According to [2] showed that laser alloying is a promising method which can be used in order to form very thick and hard layers. The results of using the PACVD technology and magnetron sputtering by [3] demonstrate that both a great surface area of actual contact of surfaces hardened with wear-resistant coatings and a low coefficient of friction can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…According to [2] showed that laser alloying is a promising method which can be used in order to form very thick and hard layers. The results of using the PACVD technology and magnetron sputtering by [3] demonstrate that both a great surface area of actual contact of surfaces hardened with wear-resistant coatings and a low coefficient of friction can be achieved.…”
Section: Introductionmentioning
confidence: 99%